Morphological asymmetry in judokas - Kuvacic, G.; Tavra, M.; Krstulovic, S. (1st scientific and professional conference on judo "Applicable research in judo" - Book of abstracts, 2015)
Judo belongs to the category of asymmetric sports, since during the realization of most of its techniques the left or the right side of the body is dominantly used. In asymmetric sport disciplines, the development of a certain degree of morphological asymmetry occurs, due to the physical and neurological demand of the locomotor system of the dominant extremity, in relation to the non-dominant one. The research showed that daily activities (the tendency towards greater functional usage of the dominant extremity in relation to the non-dominant one) can be a factor that would cause a morphological asymmetry (Steele and Mays, 1995). The basic aim of the research was to determine the morphological asymmetry in judokas of different competitive success.